Phosphorus mining efficiency declines with decreasing soil P concentration and varies across crop species. Issue 9 (29th July 2018) - Schelfhout, Stephanie; De Schrijver, An; Verheyen, Kris; De Beelde, Robbe; Haesaert, Geert; Mertens, Jan
ABSTRACT: High soil P concentrations hinder ecological restoration of biological communities typical for nutrient-poor soils. Phosphorus mining, i.e., growing crops with fertilization other than P, might reduce soil P concentrations. However, crop species have different P-uptake rates and can affect subsequent P removal in crop rotation, both of which may also vary with soil P concentration. In a pot experiment with three soil-P-levels (High-P: 125–155 mg POlsen /kg; Mid-P: 51–70 mg POlsen /kg; Low-P: 6–21 mg POlsen /kg), we measured how much P was removed by five crop species (buckwheat, maize, sunflower, flax, and triticale). Total P removal decreased with soil-P-level and depended upon crop identity. Buckwheat and maize removed most P from High-P and Mid-P soils and triticale removed less P than buckwheat, maize, and sunflower at every soil-P-level. The difference in P removal between crops was, however, almost absent in Low-P soils. Absolute and relative P removal with seeds depended upon crop species and, for maize and triticale, also upon soil-P-level. None of the previously grown crop species significantly affected P removal by the follow-up crop (perennial ryegrass). We can conclude that for maximizing P removal, buckwheat or maize could be grown.